Chronic exposure to combined carcinogens enhances breast cell carcinogenesis with mesenchymal and stem-like cell properties. - Lenora Ann Pluchino; Hwa-Chain Robert Wang (PLoS ONE, 2014)
Breast cancer is the most common type of cancer affecting women in North America and Europe. More than 85% of breast cancers are sporadic and attributable to long-term exposure to small quantities of multiple carcinogens. To understand how multiple carcinogens act together to induce cellular carcinogenesis, we studied the activity of environmental carcinogens 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and benzo[a]pyrene (B[a]P), and dietary carcinogen 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) using our breast cell carcinogenesis model. Our study revealed, for the first time, that combined NNK and B[a]P enhanced breast cell carcinogenesis chronically induced by PhIP in both non-cancerous and cancerous breast cells. Co-exposure was more potent than sequential exposure to combined NNK and B[a]P followed by PhIP in inducing carcinogenesis. Initiation of carcinogenesis was measured by transient endpoints induced in a single exposure, while progression of carcinogenesis was measured by acquisition of constitutive endpoints in cumulative exposures. Transient endpoints included DNA damage, Ras-Erk-Nox pathway activation, reactive oxygen species elevation, and increased cellular proliferation. Constitutive endpoints included various cancer-associated properties and signaling modulators, as well as enrichment of cancer stem-like cell population and activation of the epithelial-to-mesenchymal transition program. Using transient and constitutive endpoints as targets, we detected that a combination of the green tea catechins ECG and EGCG, at non-cytotoxic levels, was more effective than individual agents in intervention of cellular carcinogenesis induced by combined NNK, B[a]P, and PhIP. Thus, use of combined ECG and EGCG should be seriously considered for early intervention of breast cell carcinogenesis associated with long-term exposure to environmental and dietary carcinogens.